Src-family-tyrosine kinase Lyn is critical for TLR2-mediated NF-κB activation through the PI 3-kinase signaling pathway. Issue 7 (October 2015) - Toubiana, Julie; Rossi, Anne-Lise; Belaidouni, Nadia; Grimaldi, David; Pene, Frederic; Chafey, Philippe; Comba, Béatrice; Camoin, Luc; Bismuth, Georges; Claessens, Yann-Erick; Mira, Jean-Paul; Chiche, Jean-Daniel
TLR2 has a prominent role in host defense against a wide variety of pathogens. Stimulation of TLR2 triggers MyD88-dependent signaling to induce NF-κB translocation, and activates a Rac1-PI 3-kinase dependent pathway that leads to transactivation of NF-κB through phosphorylation of the P65 NF-κB subunit. This transactivation pathway involves tyrosine phosphorylations. The role of the tyrosine kinases in TLR signaling is controversial, with discrepancies between studies using only chemical inhibitors and knockout mice. Here, we show the involvement of the tyrosine-kinase Lyn in TLR2-dependent activation of NF-κB in human cellular models, by using complementary inhibition strategies. Stimulation of TLR2 induces the formation of an activation cluster involving TLR2, CD14, PI 3-kinase and Lyn, and leads to the activation of AKT. Lyn-dependent phosphorylation of the p110 catalytic subunit of PI 3-kinase is essential to the control of PI 3-kinase biological activity upstream of AKT and thereby to the transactivation of NF-κB. Thus, Lyn kinase activity is crucial in TLR2-mediated activation of the innate immune response in human mononuclear cells.